Application of Cublak-Cublak Suweng Traditional Game in Thematic Learning of Early Childhood Education - Masrurotul Mahmudah; Muh. Ngali Zainal Makmun (Journal of Childhood Development, 2022)
Along with the increasing sophistication of learning systems and learning facilities today, where learning can be done anytime and anywhere. This has a positive value for the presence of technology in the world of education. But besides that, there is a negative impact in that many children are not familiar with traditional games, which can be a means of learning for them and can even have a good effect on social-emotional and cognitive development. However, today's children will find it difficult to find models of traditional games independently if they are not started by the teacher or other people familiar with these classic games. This study uses a qualitative research method with an analytical descriptive approach. As for how to apply the cublak-cublak suweng game, teams or groups are played between 4-5 children. In the division of tasks, one child becomes a game table by bending over, and four become game actors. Children use small stones as tools circled between players by singing cublak-cublak suweng songs. In this game, there is a system of losing and winning. Those who fail are assigned to the game table, while those who win continue the game. The educational value of this game is that each child tries to coordinate with the other, understand and obey the game's rules, and think carefully in guessing questions. There is togetherness between the group or team. This game is straightforward and doesn't take long.